A 3D in vitro comparison of two undiluted e-cigarette aerosol generating systems. (1st April 2022) - Bishop, E.; Terry, A.; East, N.; Breheny, D.; Gaça, M.; Thorne, D.
Graphical abstract: Highlights: Air-control data from three donors across multiple years of work show donor cross-comparison is possible. Comparison of adapted Vitrocell VC10 and Borgwaldt LM4E for in vitro e-cigarette exposure in MucilAir. ePen3 e-cigarette response in MucilAir comparable across both aerosols generating system used. Allows further comparison of previously published eBox with ePen3 responses in MucilAir. New e-cigarette technology in ePen3 reduced toxicity compared to eBox and cigarette smoke. Abstract: In vitro studies play an important role in supporting the toxicological assessment of e-cigarettes, with many current methods reliant on sophisticated in vitro exposure systems designed for conventional cigarette testing. In this study, we have compared two distinct systems; the modified Vitrocell VC10 and Borgwaldt LM4E designed to deliver undiluted e-cigarette aerosol. We assessed the cytotoxicity response of 3D reconstituted lung tissue (MucilAir) exposed to undiluted aerosol from ePen3 (closed modular e-cigarette) using these two exposure systems. As the induced cytotoxicity profiles were comparable, we then compared these responses against historical eBox (open modular e-cigarette) and 3R4F reference cigarette data to show evolution of product technology. This latter approach was deemed possible by monitoring intrinsic donor-to-donor control variability over a three-year period, bridging between exposure systems and observed biological responses. Despite the differences in the technology, on a puff-by-puff basis these machines gave remarkably similar cytotoxicity profiles for ePen3, as determined by MTT, and consistency of pre-cytotoxicity markers: transepithelial electrical resistance (TEER), cilia beat frequency and cilia active area. When responses are compared as a function of exposed nicotine concentration, we see differences due to the dynamics of the exposure systems. The parity of responses between the systems in generated undiluted aerosol has allowed us to compare back to previously published eBox data, irrespective of aerosol generating system and MucilAir donor, showing how evolution from open systems to podmod e-cigarette design can make a step change in the cytotoxicity profile of the product.